Universidade Federal de CatalãoSIMULATION AS A TEACHING STRATEGY FOR TEACHING AND LEARNING STRENGTH OF MATERIALS - Linhares, Elton Brasil; Stoppa, Gabriel Percival; Stoppa, Marcelo Henrique (Brazilian Journal of Production Engineering, 2025)
Teaching through expository and dialogued classes of abstract concepts using only blackboards and chalk is still very common in engineering courses. For the Materials Strength discipline, present in Civil Engineering courses, this reality is no different. Shifting to a more concrete approach can encourage active student participation and develop understanding of these concepts. This work aims to present a pedagogical proposal that integrates simulation via the Finite Element Method (FEM) with the free software FreeCAD, as a teaching strategy for the practical teaching of mechanical concepts. For this, data obtained through mechanical testing of cubic test specimens (CPs) with 20 mm edges, 3D printed with PLA material using different filling patterns and theoretical knowledge, was used as a reference. The theoretical and simulated results were compared and showed a good approximation for the stress and strain values, two fundamental concepts in the discipline, highlighting the importance of the methodology as a teaching and learning tool. Furthermore, the proposal promotes an accessible, participatory methodology that adds technological knowledge and encourages innovative pedagogical practices to engineering courses.